Toxicity and Antioxidant Potential Screening of Extracts from Five Marine Sponges Collected off Zamboanga Peninsula, Philippines - Francisco, Jayson T.; Uy, Mylene M. (Asian Journal of Biological and Life Sciences, 2016)
Marine sponges contain unique secondary metabolites that are known to exhibit significant biological properties and can be used for various applications. In this study, five (5) marine sponges were collected off the coast of the Zamboanga Peninsula, Philippines and taxonomically identified as Petrosia sp., Oceanapia ramsayi, Clathria sp., Ancorina cerebrum and Haliclona fascigera. The marine sponges were sequentially extracted with ethyl acetate:methanol and ethanol:water to give the nonpolar and polar extracts, respectively. The sponge extracts were investigated for toxicity using the brine shrimp lethality assay and antioxidant properties through the 1,1-Diphenyl-2-picrylhydrazyl radical-scavenging assay and phosphomolybdenum method. Results show that almost all of the sponge extracts possess chronic toxicity against the brine shrimp Artemia salina Leach as LC50 values were observed to be less than 1000 ppm, with the nonpolar and polar extracts of O. ramsayi possessing the lowest LC50 values of 48.78 and 736.21 ppm, respectively. All sponge extracts exhibited low antioxidant properties with percent radical scavenging activity values from 0 to 22.74% and total antioxidant capacity value ranges of 17.79 – 341,04 Ascorbic Acid Equivalence (AAE) and 41.23 – 445.73 Butylated Hydroxytoluene Equivalence (BHTE).
Keywords: Bioactivity; Marine sponges; Radical-scavenging; Total antioxidant; Toxicity